ReishiMax, mushroom based dietary supplement, inhibits adipocyte differentiation, stimulates glucose uptake and activates AMPK - Sliva Daniel; Lane Brandon; Thyagarajan-Sahu Anita (BMC, 2011)
Abstract Background Obesity is a health hazard which is closely associated with various complications including insulin resistance, hypertension, dyslipidemia, atherosclerosis, type 2 diabetes and cancer. In spite of numerous preclinical and clinical interventions, the prevalence of obesity and its related disorders are on the rise demanding an urgent need for exploring novel therapeutic agents that can regulate adipogenesis. In the present study, we evaluated whether a dietary supplement ReishiMax (RM), containing triterpenes and polysaccharides extracted from medicinal mushroom Ganoderma lucidum, affects adipocyte differentiation and glucose uptake in 3T3-L1 cells. Methods 3T3-L1 pre-adipocytes were differentiated into adipocytes and treated with RM (0-300 μg/ml). Adipocyte differentiation/lipid uptake was evaluated by oil red O staining and triglyceride and glycerol concentrations were determined. Gene expression was evaluated by semi-quantitative RT-PCR and Western blot analysis. Glucose uptake was determined with [3H]-glucose. Results RM inhibited adipocyte differentiation through the suppresion of expression of adipogenic transcription factors peroxisome proliferator-activated receptor-γ (PPAR-γ), sterol regulatory element binding element protein-1c (SREBP-1c) and CCAAT/enhancer binding protein-α (C/EBP-α). RM also suppressed expression of enzymes and proteins responsible for lipid synthesis, transport and storage: fatty acid synthase (FAS), acyl-CoA synthetase-1 (ACS1), fatty acid binding protein-4 (FABP4), fatty acid transport protein-1 (FATP1) and perilipin. RM induced AMP-activated protein kinase (AMPK) and increased glucose uptake by adipocytes. Conclusion Our study suggests that RM can control adipocyte differentiation and glucose uptake. The health benefits of ReishiMax warrant further clinical studies.